Identification factors influencing e-learning satisfaction during COVID -19 pandemic period among students at a Malaysia private institution / Han Kok Heng …[et al.] - Han, Kok Heng; Md. Ithnan, Izwan Harith; Chun, Keat Yeap; Pei, Yee Lai (UiTM Press, 2021)
The rapid occurrences of Corona Virus Disease (Covid-19) have posed various challenges to our society, including the quality of education system in Malaysia. The current study aims to first measure the impact of demographic variables (gender, age and education level) and non-demographic variables (perceived usefulness, perceived ease of use and technological factor) on e-learning satisfaction among students from a higher education institution in Malaysia, and to construct a student satisfaction prediction model subsequently. A structured questionnaire survey was administered to a total of 344 respondents and the statistical analysis of Chi-Square test and Multiple Regressions was performed. The result of the study reveals that satisfaction of students on e-learning experience during the pandemic is significantly correlated to gender. The study further shows that three dominant variables, namely perceived usefulness, perceived ease of use and technological factor are significant factors that influence the satisfaction level of students’ learning in the e-learning environment. The findings of the study will be beneficial to policy makers to identify the level of student satisfaction on e-learning education during the COVID-19 pandemic and may provide evidence-based data to improve the learning performance of students.